Adaptive bionic joint base on the flexibility feature of ostrich intertarsal joint. (April 2020) - Zhang, R; Cao, Q Q; Ling, L; Kong, L X; Wang, C; Su, B; Wen, L G; Li, J Q
Abstract: The joints of traditional foot robots are generally designed as power-driven articulated rotary motion, but this design has some problems such as poor flexibility and adaptability. To optimize joints, this paper selected the African ostrich intertarsal joint which could move at high speed in complex terrain as a biomimetic prototype. Based on the motion acquisition and reverse engineering three-dimensional reconstruction of the intertarsal joint, a rope-driven spherical sub-bionic joint was designed. The angle curves of the bionic joints under different ground conditions were obtained through the hard ground and the motion tests of three different softness sands (medium with different particle sizes). Results showed that the proportion of the vacant period was 35%, 49%, 62% and 63% when the bionic joint moved on the hard ground and three soft grounds (the particle size particles are arranged from large to small), . The range of variation gradually becomes larger, similar to the variation trend of the intertarsal joint during ostrich locomotion. The bionic joint was able to absorb joint impact through the relative slippage of the joint surface and expansion/contraction of the rope, and maintain flexibility when passing through different degrees of softness.